2019
DOI: 10.3390/md17030158
|View full text |Cite
|
Sign up to set email alerts
|

A New Sesquiterpenoid Aminoquinone from an Indonesian Marine Sponge

Abstract: Sponges are a well-known bioresource for bioactive compounds. In this study, antibacterial activity-guided fractionation of the extract from an Indonesian marine Dactylospongia elegans sponge led to the discovery of four merosesquiterpenoids, namely, a new sesquiterpenoid aminoquinone nakijiquinone V (1), along with illimaquinone (2), smenospongine (3), and dyctioceratine C (4). The structure of compound 1 was elucidated by 1D and 2D NMR as well as by LC-HRESIMS data analysis. Compounds 2–4 showed moderate to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 26 publications
2
10
0
Order By: Relevance
“…Methanol is preferred as an organic solvent to extract multi-variable types of hydrophobic compounds because it can extract both non-polar and polar compounds, as well as proteins. 27 This finding was in agreement with Touti et al 28 who found very weak antibacterial activity in the aqueous extract (water) from seven Tunisian marine sponges compared to the organic phase of ethyl acetate extracts. Another report by Ankisetty and Slattery 29 suggested that the mixture of dichloromethane/ methanol (1:1 v/v) to extract Xetospongia sp.…”
Section: Discussionsupporting
confidence: 90%
“…Methanol is preferred as an organic solvent to extract multi-variable types of hydrophobic compounds because it can extract both non-polar and polar compounds, as well as proteins. 27 This finding was in agreement with Touti et al 28 who found very weak antibacterial activity in the aqueous extract (water) from seven Tunisian marine sponges compared to the organic phase of ethyl acetate extracts. Another report by Ankisetty and Slattery 29 suggested that the mixture of dichloromethane/ methanol (1:1 v/v) to extract Xetospongia sp.…”
Section: Discussionsupporting
confidence: 90%
“…In our ongoing investigation of new antibiotic drug leads from sponges of Sangihe Islands, North Sulawesi Indonesia (Balansa et al 2017(Balansa et al , 2019Azhari et al 2018), we noticed that the crude extract of a sponge collected in Enepahembang East Tahuna showed a strong antibacterial activity against three ESKAPE bacteria (S. aureus, A. baumannii and K. pneumoniae) and three fish pathogenic bacteria (A. hydrophila, V. parahaemolyticus, and E. tarda). This encouraged us to further identify the sponge species and investigate its active component, leading to the discovery of agelasines B and D from an Agelas sp.…”
Section: Introductionmentioning
confidence: 97%
“…Other compounds isolated from Sulawesi included nakijiquinone V ( 83 ), isolated from Dactylospongia elegans from Tahuna, Sangihe Islands, North Sulawesi [ 39 ]. It has three methyl groups attached to a decalin system with an exocyclic double bond [ 39 ] ( Figure 6 ).…”
Section: Marine Invertebratesmentioning
confidence: 99%
“…Other compounds isolated from Sulawesi included nakijiquinone V ( 83 ), isolated from Dactylospongia elegans from Tahuna, Sangihe Islands, North Sulawesi [ 39 ]. It has three methyl groups attached to a decalin system with an exocyclic double bond [ 39 ] ( Figure 6 ). Another was a new meroditerpene—namely, Halioxepine ( 84 ), which was isolated from an Indonesian marine sponge from the genus Haliclona collected in Baubau, Southeast Sulawesi [ 40 ].…”
Section: Marine Invertebratesmentioning
confidence: 99%